Race level comparison and variability analysis of 100 m freestyle sprinters competing in the 2019 European championships. (4th May 2022) - Morais, Jorge E; Barbosa, Tiago M; Lopes, Tiago; Marinho, Daniel A
ABSTRACT: This study aimed to (i) compare the race performance of the swimmers with better performances and poorer performances during all sections of a 100 m freestyle event and (ii) compare stroke kinematics variables between tiers and analyse their stability in each tier. The sample was composed of 88 swimmers that participated in the 100 m Freestyle event at the 2019 LEN European Junior Championships. Speed achieved the largest difference between tiers in section (S) S0-15 m of lap #1 (mean difference = −0.109 s, p < 0.001). During the clean swim and finish phases, the stroke length and stroke index presented significant differences (p < 0.05) between tiers in all sections of the race (stroke frequency did not). Significant variances were noted for both tiers in all variables in both laps. Swimmers in tier #1 were significantly faster than swimmers in tier #2 especially in sections related to the push-off against a solid (block or wall), and finish. A significant variance was noted by both tiers during the race with a moderate-to-high normative stability. Coaches are advised to analyse and understand the swimmers' within-lap stability, which can give deeper details about their swimmers' behaviour during the 100 m freestyle race.